2017
DOI: 10.3847/1538-4357/835/2/154
|View full text |Cite
|
Sign up to set email alerts
|

Are the Formation and Abundances of Metal-poor Stars the Result of Dust Dynamics?

Abstract: Large dust grains can fluctuate dramatically in their local density, relative to the gas, in neutralturbulent disks. Small, high-redshift galaxies (before reionization) represent ideal environments for this process. We show via simple arguments and simulations that order-of-magnitude fluctuations are expected in local abundances of large grains (>100 Å) under these conditions. This can have important consequences for star formation and stellar metal abundances in extremely metal-poor stars. Low-mass stars can… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 159 publications
(199 reference statements)
0
6
0
Order By: Relevance
“…Because high-density regions can have enhanced/suppressed dust-to-gas ratios in large grains (which contain a large fraction of the metal mass), this can have interesting implications for stellar abundances. Hopkins & Conroy (2015) use similar simulations, coupled to a specific dust chemistry model, to explore consequences for abundance patterns in metal-poor stars, and suggest that certain observed chemical signatures in these stars may demonstrate variable dust-to-gas ratios in their progenitor clouds. Hopkins (2014b) use a simple analytic model to further explore the consequences for stellar abundance variations across present-day star forming clouds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because high-density regions can have enhanced/suppressed dust-to-gas ratios in large grains (which contain a large fraction of the metal mass), this can have interesting implications for stellar abundances. Hopkins & Conroy (2015) use similar simulations, coupled to a specific dust chemistry model, to explore consequences for abundance patterns in metal-poor stars, and suggest that certain observed chemical signatures in these stars may demonstrate variable dust-to-gas ratios in their progenitor clouds. Hopkins (2014b) use a simple analytic model to further explore the consequences for stellar abundance variations across present-day star forming clouds.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, several studies have suggested that dust grains in GMCs or neutral galactic disks should exhibit similar fluctu-E-mail:hlee2@mit.edu ations (Padoan et al 2006;Hopkins 2014b;Hopkins & Conroy 2015) -in terms of the aerodynamic drag equations, a grain of diameter ∼ 0.1−1 µm in a typical GMC is analogous to a meter-sized boulder in a protoplanetary disk. And observations have identified small-scale (∼ 0.01−1 pc) fluctuations in the local dust-to-gas ratio of large grains in a number of nearby molecular clouds (Thoraval et al 1997(Thoraval et al , 1999Abergel et al 2002;Flagey et al 2009;Boogert et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…30 As discussed in Paper II, the RDI could be an important part of observed phenomena ranging from the well-studied clumpiness, substructure, and turbulence in the dusty AGN 'torus' (see e.g. Krolik & Begelman 1988;Nenkova et al 2008;Mor, Netzer & Elitzur 2009;Hönig & Kishimoto 2010, and references therein), time variability in AGN dust obscuration (McKernan & Yaqoob 1998;Risaliti, Elvis & Nicastro 2002), AGN winds driven by radiation pressure on dust (Murray et al 2005;Elitzur & Shlosman 2006;Miller, Turner & Reeves 2008;Wada, Papadopoulos & Spaans 2009;Roth et al 2012), observed dust-gas segregation in GMCs (Padoan et al 2006) and abundance anomalies sourced by these (Hopkins 2014;Hopkins & Conroy 2017), dust growth and coagulation (believed to occur primarily in the cold, dense ISM; Draine 2003 and references therein), dust chemistry/cooling physics critical for star formation and formation of complex organic compounds and molecules (Goldsmith & Langer 1978;Dopcke et al 2013;Chiaki et al 2014;Ji, Frebel & Bromm 2014), radiation-pressure-driven outflows from massive stars (Murray et al 2005;Krumholz, Klein & McKee 2007;Hopkins, Quataert & Murray 2011;Grudić et al 2016), and thermal regulation of proto-star formation via heating dust in coupled dust-gas cores (Guszejnov, Krumholz & Hopkins 2016).…”
Section: Sne Ejectamentioning
confidence: 99%
“…They may fundamentally alter the ability of radiation pressure from massive stars to drive outflows and source local turbulence (a subject of considerable interest and controversy; see Murray et al 2005;Thompson et al 2005;Krumholz et al 2007;Schartmann et al 2009;Hopkins et al 2011Hopkins et al , 2013Hopkins et al , 2014Guszejnov et al 2016;Grudić et al 2018). They will also directly source dust-togas fluctuations, which can in turn drive abundance anomalies in next-generation stars (Hopkins 2014;Hopkins & Conroy 2017), as well as altering the dust growth, chemistry, and cooling physics of the clouds (Goldsmith & Langer 1978;Dopcke et al 2013;Ji et al 2014;Chiaki et al 2014).…”
Section: Astrophysical Applicationsmentioning
confidence: 99%